Long-Term Anatomical and Hearing Outcomes of Canal Wall down Tympanoplasty for Tympano-Mastoid Cholesteatoma: A 20-Year Retrospective Study - Salvatore Ferlito; Ignazio La Mantia; Federico Merlino; Salvatore Cocuzza; Arianna Di Stadio; Giovanni Cammaroto; Ricardo Bartel; Gianluca Fadda; Giannicola Iannella; Quentin Mat; Stéphane Gargula; Justin Michel; et al. (Life, 2022)
Background: to evaluate the residual rate and the functional results after ten years from canal wall down tympanoplasty (CWD) for tympano-mastoid cholesteatoma. Methods: All the patients undergoing CWD for chronic otitis media with cholesteatoma at our ENT University Department between January 2002 and December 2022 were initially assessed. We performed clinical and diagnostic evaluation at baseline, 6 months, and then every year until an average follow-up of 10 years was obtained. Patients were consequently divided into two groups according to the presence (group A) or absence (group B) of the stapes superstructure. Results: After the selection process, 176 ears were included. The presence of the stapes superstructure was associated with better hearing outcomes (rate of patients < 30 dB) at 6 months (91.42% vs. 74.46%; p = 0.001) and 10 years (74.46% vs. 24.11%; p < 0.001). Residual cholesteatoma was reported in 10 ears, which included 2/35 ears in group A (5.71 %) and 8/141 in group B (5.67 %) (p = 0.993). The recurrent cholesteatoma rate was respectively 1/35 (2.85%) vs. 3/141 (2.18%) (p = 0.516). Conclusions: the CWD approach to cholesteatoma allows for effective long-term anatomical disease control and good hearing results when the stapes superstructure is preserved.